Late Middle Jurassic aridification event in the Qaidam Basin, Northwest China: palynological and geochemical evidences - Xie, Wen-Quan; Wang, Wen-Hui; Tan, Jing-Qiang; Liu, Zhao-Jun; Wang, Yong; Song, Xue-Qi; Mansour, Ahmed (Palaeoworld, 2024)
Jurassic is characterized by a highly fluctuating climate. During the late Middle to Late Jurassic, Northwest China, including the Qaidam Basin, underwent a major climate transition from humid to arid conditions. In this study, we focused on the climate transitional interval (Bathonian Stage, Jurassic) and conducted high-resolution palynological and geochemical analysis to constrain more accurately this aridification event. We found that at the uppermost part of the Middle Jurassic Shimengou Formation, the relative abundance of Classopollis pollen increases along with a dramatic drop in the chemical index of alteration (CIA) and C-value, indicating a significant climate transition from humid to arid conditions during late Bathonian. Other geochemical proxy indicators, such as salinity and bulk carbonate carbon and oxygen isotopes, suggest the lacustrine environment of a closed saline lake. These significant changes indicate an environment of flourished xerophytic vegetation, weakened chemical weathering and enhanced lake salinization in the Qaidam Basin during late Bathonian, a critical turning point of the late Middle Jurassic climate from humid to arid conditions in the area, instead of Callovian (the red bed) as previously suggested.